2013
DOI: 10.1080/01932691.2013.769109
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Chain Microstructure Magnetic Emulsions in Magnetic Field

Abstract: Abstract. The work deals with the experimental study of the emulsion whose dispersion medium is a magnetic fluid while the disperse phase is formed by a glycerin-water mixture. It is demonstrated that under effect of a magnetic field chain aggregates form from the disperse phase drops. Such emulsion microstructure change affects its macroscopic properties. The emulsion dielectric permeability and specific electrical conductivity have been measured.It is demonstrated that under the effect of relatively weak ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Exposure to an external magnetic field leads to a change in the microstructural state of the sample due to the association of ferrofluid droplets into chain structures (figure 2(b)). A distinctive feature of this emulsion from those previously synthesized and studied in other works [24][25][26][27][28][29][30] is the simultaneous presence of high magnetic and dielectric properties of the dispersed phase.…”
Section: Methodsmentioning
confidence: 79%
“…Exposure to an external magnetic field leads to a change in the microstructural state of the sample due to the association of ferrofluid droplets into chain structures (figure 2(b)). A distinctive feature of this emulsion from those previously synthesized and studied in other works [24][25][26][27][28][29][30] is the simultaneous presence of high magnetic and dielectric properties of the dispersed phase.…”
Section: Methodsmentioning
confidence: 79%
“…Refs. [48,49]), the formation of chained structures of ferrofluid droplets, [50] and the effect of these structures on the emulsion electrical properties [51]. Finally, it is worth mentioning the recent work of Zakinyan and Zakinyan [52] who succeed on producing an emulsion of ferrofluid microdrops using a rotating magnetic field and showed that the resulting magnetic torque of the emulsion can be enhanced with respect that observable in the pure ferrofluid.…”
Section: Introductionmentioning
confidence: 98%
“…The cause of strong optical anisotropy may be the orientation of chain aggregates in a magnetic field (Fig. 8) [18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%